Photoreduction of Cr(VI) Catalyzed by TiO2-Lignin - Yuniar Yuniar; Endang Tri Wahyuni; Nurul Hidayat Aprilita (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2017)
In order to increase the activity of TiO2 photocatalyst, preparation and characterization of TiO2-lignin and its activity on Cr(VI) photoreduction have been carried out. TiO2-lignin was prepared by mixing TiO2 powder with lignin powder in water-ethanol followed by stirring for 24 h and calcination at 400°C. The crystal structure characterizations were performed by X-ray diffraction (XRD), Lignin was identified using FT-IR whereas photoreduction of Cr(VI) was conducted in a batch reactor. The effect of TiO2 content on TiO2-lignin, irradiation time, weight of photocatalyst and initial concentration of Cr(VI) were studied to obtain effectiveness of photoreduction. Activity of TiO2-lignin on the photoreduction of Cr(VI) showed higher result than TiO2. The increased of TiO2 content in TiO2-lignin result in higher Cr(VI) photoreduction and gave maximum yield at mass ratio of TiO2/lignin 2:1. The irradiation time, weight of TiO2-lignin photocatalyst and initial concentration of Cr(VI) obtained for maximum Cr(VI) photoreduction are 40 h, 50 mg and 1 mg/L respectively which reduced Cr(VI) by 81.44%. Keywords: TiO2-lignin, Cr(VI) ion, photoreduction